An open source tool for reliability evaluation of distribution system using Monte Carlo simulation - Bhargava Chitumodhu; Renuka Loka (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
As the demand for electricity is shooting exponentially, reliable supply of electrical energy from generation to customer is the challenging task faced by utilities. Though generation and transmission can be maintained at hundred percent reliability, reliability of entire system cannot be assured unless focus is laid on distribution system. Most of the faults are occurring on the distribution system which is directly connected to different customers. Hence, we need to intensify the attention at distribution level. Due to deregulation, private players are evolving in distribution sector which complicates power system data exchange and information integration.   To cope with this scenario, reliability evaluation of distribution system through Monte Carlo Simulation (MCS) with feature of interoperability for Bus 2 of RBTS system has been introduced and analyzed using SOAP web services. Simulation is performed by developing a web application in Java and is deployed on the Glass-fish server using JAX-WS. The intent behind this proposed model is to use the internet as the transactional tool and exposing the functionality of the program for reliability evaluation for utilities to use and providing facility of interoperability through standards refinement and integration into profiles.